The state of nutrition and the self-assessment of symptoms of depression in the group of seniors living in the countryside of Lublin province – preliminary report - Bartoszek, Agnieszka; Domżał-Drzewicka, Renata; Kachaniuk, Hanna; Kocka, Katarzyna; Muzyczka, Katarzyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : The incidence of malnutrition increases together with the number of chronic diseases and medications taken daily. There are also other factors causing changes in the nutrition of the elderly, raising the risk of undernourishment. Such factors include difficulties with daily shopping, meal preparation and other everyday activities, hindering access to food with proper quantitative and qualitative properties. The nutritional state of the elderly is influenced not only by somatic disorders, but also by mental disorders such as depression. Aim : To define the relationship between the nutritional state of the elderly living in their home environment and the incidence of depression. Material and methods: The described sample consisted of 116 (100%) elderly persons living in the Lubelskie Voivodeship, using the services carried out within primary healthcare. The nutritional state of the elderly was assessed with the use of the full version of the Mini Nutritional Assessment (MNA) questionnaire. In order to determine the intensity of depression symptoms, the Geriatric Depression Scale (GDS) (the 15-item version by Yesavage) was applied. Results : During analysis of the impact of depression on malnutrition risk, a correlation with a high statistical significance level was found. Malnutrition was significantly more often identified in people in whom the GDS scale revealed severe depression (p = 0.00002). The risk of depression has a substantial impact on nutritional state. The nutritional state of the elderly deteriorates together with the increase of the risk of depression. Conclusions : In over 48% of respondents, including those living with their families, an intensification of depression symptoms was found.